Technology Facilitates Physical Activity Through Gamification: A Thematic Analysis of an 8-Week Study - Kappen, Dennis L.; Mirza-Babaei, Pejman; Nacke, Lennart E. (Frontiers in Computer Science, 2020)
Gamification technology has served as behaviour change mechanism for increasing the engagement and motivation of consumers in many areas including health and wellness domains. While research on physical activity (PA) and motivation to participate in PA in the context of older adults exist, there are fewer studies on the usage of gamified technology by older adults over longer periods of time. We conducted a mixed-method, eight-week, synchronous, three-condition experimental study with older adults in the 50+ age group. Participants were randomized into Group 1 (gamified), Group 2 (non-gamified) and a control group. The weekly semi-structured interview questions focused on their motivation for PA, setting up goals, accomplishments, fears or barriers, rewards and tracking in PA. Thematic analysis of the interview data showed distinct variations in emergent themes for the three groups over an eight-week period. This further indicated that gamification elements can be customized to participants for older adults and tailored to suit their current health conditions and prevalent barriers to participate in PA.